Efektivitas E-Modul Berbasis Aplikasi Canva pada Mata Pelajaran Pendidikan Agama Islam (PAI) di SMAN 1 Solok Selatan - Nisa, Qhairin; Sulaiman, Sulaiman (TSAQOFAH, 2025)
Low student motivation in the Islamic Religious Education (Pendidikan Agama Islam or PAI) subject has become a major obstacle in the learning process at SMAN 1 Solok Selatan, as indicated by passive attitudes, lack of enthusiasm, and limited interest in conventional teaching methods. This study aims to determine the effectiveness of using a Canva-based e-module in increasing students’ learning motivation in PAI. A quantitative method with a quasi-experimental approach and 2x2 factorial design was employed. The population consisted of all tenth-grade students (333 individuals), with a random sample comprising class E7 as the experimental group (31 students) and class E8 as the control group (30 students). Research instruments included a learning motivation questionnaire and multiple-choice test items. Data were analyzed using Paired Sample t-Test, Independent Sample t-Test, and N-Gain Score calculation with SPSS version 30. The results show that the use of the Canva-based e-module significantly increased students' learning motivation, with an average N-Gain of 56.84% in the experimental class (moderately effective category), while the control class experienced a decrease in motivation with an N-Gain of -16.24% (ineffective category). The study concludes that the Canva e-module is an effective learning medium for enhancing student motivation in PAI. Its implications highlight the importance of integrating technologies such as Canva into religious education as a strategic approach to creating more engaging, interactive, and relevant learning experiences for today’s digital generation.